(3HOGjI Gdabjg (B/s - (3GdYLej, SGdes ((3GdchjJ (B:s (3OGQ EjdGa GdOhdjIs, 2021)
(3jJfGhd cJGH (B((3HOGjI Gdabgjg(B) (3hGdPj bGe HJCdjag O(B. (3SGde GdYLej, ehVhY (B((3Gdabg(B) (3gPG GdcJGH eNJUQ aj Gdabg, ebQhf HGdCOdI GdTQYjI ef cJGH Gddg GdYRjR, hUMjM GdSfI GdfHhjI GdTQjaI, LeYJ eGOJg ef cJGH GdTQM GdeeJY Ydi RGO GdeSJfbY, ddYdGeI GHf YKjejf, Ohf GdJRGe HLejY JQLjMGJg, hCVGa Edjg GdeDda CbhGd ZjQg ef GdabgGA, hRGO Ydjg eG JOYh GdMGLI Edjg ef EjVGM eYfi Ch HjGf Naj, Ke cJHg HWQjbI JfGSH GdJCdja GdYUQj ef fGMjI GdJaQjZ hGdJbSje, eSGgeI aj EYWGA fHPI JYQjajI ehLRI dCHhGH Gdabg, hNWhI Chdi aj JOQjS GdeHJOFjf(B. s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3Gdabg GdESdGejs